Implementation climate and clinic personnel attitudes in primary care towards a mental health and drug use preventive intervention for hispanic families: preliminary findings - Lozano, Alyssa; Weinstein, Elliott R.; Lee, Tae Kyoung; Smith, Justin D.; Brown, C. Hendricks; Prado, Guillermo (Frontiers in Health Services, 2025)
Despite the availability of preventive interventions to address mental health and drug use among Hispanic adolescents, few are implemented in real-world settings. Favorable attitudes towards evidence-based practices and a better implementation climate can facilitate the successful execution of interventions in real-word settings to ameliorate health disparities among Hispanic youth. The purpose of this study was to investigate how implementation climate influences attitudes toward a mental health and drug use preventive intervention for Hispanic families at the individual and clinic level. Participants included 73 clinic personnel from 18 primary care clinics that were part of an effectiveness-implementation hybrid Type 1 study in South Florida. Clinic personnel completed the Implementation Climate Scale and Evidence-based Practice Attitude Scale. Using hierarchal linear modeling, we examined: (1) whether individual differences in implementation climate were associated with individual attitudes towards an evidence-based practice within clinics, and (2) whether clinic-level differences in mean implementation climate were associated with clinic-level differences in attitudes towards an evidence-based practice. At the individual level, there was a significant positive relationship between individual implementation climate and attitudes toward the evidence-based practice. Implementation climate varied significantly among individuals. At the clinic level, clinics with higher average implementation climate did not show significantly different average attitudes towards the mental health and drug use preventive intervention. Understanding implementation climate and attitudes toward evidence-based practices can inform tailored implementation strategies for the unique needs of primary care settings to address drug use and mental health disparities among Hispanic youth.